2000
DOI: 10.1002/(sici)1099-0739(200005)14:5<229::aid-aoc977>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic complexes with biological molecules. XIV. Biological activity of dialkyl and trialkyltin(IV) [meso-tetra(4-carboxy- phenyl)porphinate] derivatives

Abstract: The effects of several organotin(IV) meso‐tetra(4‐carboxyphenyl)porphinate] derivatives with the general formula (R2Sn)2TPPC and (R3Sn)4TPPC (R = Me, Bu, Ph) were tested in vivo on ascidian embryonic development. Embryos at the two‐cell stage were incubated in 1 × 10−5 or 1 × 10−7 M solutions of various compounds. The ligand, [meso‐tetra(4‐carboxyphenyl)porphine] (H4TPPC) was toxic at 1 × 10−5 M, because development was blocked at an early gastrula stage, whereas 1 × 10−7 M H4TPPC allowed the eggs to develop u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Furthermore, attention has been addressed on the interaction with DNA of newly synthesized compounds [6,10,12] and on the antineoplastic effect of several organotin(IV) compounds [13][14][15].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, attention has been addressed on the interaction with DNA of newly synthesized compounds [6,10,12] and on the antineoplastic effect of several organotin(IV) compounds [13][14][15].…”
Section: Introductionmentioning
confidence: 67%
“…On the other hand, the biological effects of organotin(IV) derivatives have been the focus of research in embryos and gametes of Ascidians [7,10,11]. Furthermore, attention has been addressed on the interaction with DNA of newly synthesized compounds [6,10,12] and on the antineoplastic effect of several organotin(IV) compounds [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, those data mainly correspond to adult stage animals and chronic exposure conditions. Reported effects of TBT in ascidian and sea urchin embryos and larvae include inhibition of the oxidative phosphorylation in the mitochondria and impairing of the intracellular Ca +2 homeostasis (Cima et al, 1996a(Cima et al, , b, 1998Girard et al, 1997Girard et al, , 2000Mansueto et al, 2000). Furthermore, Lignot et al (1998) reported effects of TBT on the osmoregulatory capacity of crustacean larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Girard et al (2000) obtained toxic effects on larval survival and growth of P. lividus larvae after exposure of eggs to 0.03-0.3 lg l )1 of TBT, suggesting that concentrations of TBT with no effect on the embryonic development could affect the sea urchin larval cycle and metamorphosis. Organoestanic compounds like TBT have been found to damage the embryonic and larval development of Ciona intestinalis in the 0.1-10 lM concentration range (Mansueto et al, 1993a, b;Maggio et al, 1994;Gianguzza et al, 1996;Pellerito et al, 1997Pellerito et al, , 1998Mansueto et al, 2000). In contrast, our results showed toxic effects of TBT at concentrations of a nanomolar range (EC 50 = 22 nM), although the incubation times in our toxicity tests are higher (20 h).…”
Section: Discussionmentioning
confidence: 99%
“…As previously showed, these compounds as well as other similar porphyrin derivatives have a photo-independent cytotoxic effect (14)(15)(16)(17). In fact, we demonstrated that (Bu 2 Sn) 2 TPPS and (Bu 3 Sn) 4 TPPS compounds induce the apoptotic death of A375 human melanoma cells without being irradiated (18), causing an arrest of cell proliferation as well, when used at lower concentrations (19).…”
Section: Apoptosis and Cell Growth Arrest In A375 Human Melanoma Cellmentioning
confidence: 99%